The utility of peer-support in enhancing the treatment of incarcerated sexual offenders. Issue 1 (9th April 2018) - Perrin, Christian; Frost, Andrew; Ware, Jayson Barry
Abstract : Purpose: In the quest to maximize treatment gains, recent research has shifted focus from treatment itself to the context in which treatment takes place. Such investigations have alluded to rehabilitative climate, therapeutic alliance, prison social climate, and the efficacy of group process. The purpose of this paper is to review peer-support as a mechanism via which these goals might be reached. Design/methodology/approach: A review of the literature on peer-support in carceral settings was undertaken in February 2017. Findings: While there is very little research exploring peer-support in the context of offender rehabilitation, there are some promising signs from many qualitative investigations that peer-led roles can bridge many gaps in support within the therapeutic context. Research limitations/implications: More research on the potential negative impact of peer-support in carceral setting is needed. Practical implications: This paper proposes that the implementation of peer-support programs that operate alongside treatment interventions represent an encouraging direction for the future. It is argued that prisoner-led peer-support initiatives that are characterized by shared problem solving and reciprocal emotional support can greatly reduce the anxiety prisoners face surrounding treatment. It is suggested that, through peer-support, treatment gains may be enhanced and better assimilated into program-completers' lives. Social implications: Peer-support may assist current treatment approaches with sexual offenders and could therefore potentially contribute to reductions in recidivism. Originality/value: This paper is the first to review peer-support in the context of imprisonment and offender therapy. It therefore provides an important status update for future researchers wishing to investigate this topic, and outlines several priorities that such research might interrogate further.